Identification and CRISPR/Cas9 Inactivation of the C1s Protease Responsible for Proteolysis of Recombinant Proteins Produced in CHO Cells. Issue 9 (10th June 2019) - Li, Sophia W.; Yu, Bin; Byrne, Gabriel; Wright, Meredith; O'Rourke, Sara; Mesa, Kathryn; Berman, Phillip W.
Abstract: Proteolysis associated with recombinant protein expression in Chinese Hamster Ovary (CHO) cells has hindered the development of biologics including HIV vaccines. When expressed in CHO cells, the recombinant HIV envelope protein, gp120, undergoes proteolytic clipping by a serine protease at a key epitope recognized by neutralizing antibodies. The problem is particularly acute for envelope proteins from clade B viruses that represent the major genetic subtype circulating in much of the developed world, including the US and Europe. In this paper, we have identified complement Component 1's (C1s), a serine protease from the complement cascade, as the protease responsible for the proteolysis of gp120 in CHO cells. CRISPR/Cas9 knockout of the C1s protease in a CHO cell line was shown to eliminate the proteolytic activity against the recombinantly expressed gp120. In addition, the C1s −/− MGAT1 − CHO cell line, with the C1s protease and the MGAT1 glycosyltransferase knocked out, enabled the production of unclipped gp120 from a clade B isolate (BaL‐rgp120) and enriched for mannose‐5 glycans on gp120 that are required for the binding of multiple broadly neutralizing monoclonal antibodies (bN‐mAbs). The availability of this technology will allow for the scale‐up and testing of multiple vaccine concepts in regions of the world where clade B viruses are in circulation. Furthermore, the proteolysis issues caused by the C1s protease suggests a broader need for a C1s‐deficient CHO cell line to express other recombinant proteins that are susceptible to serine protease activity in CHO cells. Similarly, the workflow described here to identify and knockout C1s in a CHO cell line can be applied to remedy the proteolysis of biologics by other CHO proteases. Abstract : Proteolysis associated with recombinant protein expression in Chinese Hamster Ovary (CHO) cells has hindered the development of biologics including HIV vaccines. When expressed in CHO cells, the recombinant HIV envelope protein, gp120, undergoes proteolytic clipping by a serine protease at a key epitope recognized by neutralizing antibodies.